Estrategias de política pública para la competitividad del Programa Ruta Turística Don Vasco, 2015-2017 - Rodríguez Reyes, María Eugenia (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
This research presents a proposal for the analysis of the factors that were determining factors in competitiveness in the municipalities that make up the Don Vasco Tourist Route, including the municipality of Morelia, taking the years 2015 and 2017 as a reference, for which a cluster conglomerate was carried out hierarchical, to group municipalities that share common characteristics. For the purpose of this analysis, the factors that could affect competitiveness were determined, such as: public policy programs focused on tourism, tourist attraction services, recreational services complementary to tourism, transportation service, tourist training, infrastructure and investment and quality in infrastructure. Later it was determined that the municipalities with the most infrastructure in these areas described above are Morelia as leader, followed by Uruapan, Pátzcuaro and Zamora. While the municipalities with the lowest performance are Ziracuaretiro and Tingambato, which represent deficiencies in infrastructure in general. Based on the foregoing, proposals are made in the field of tourism aimed at how to achieve improvement and performance of the municipalities that present this problem?

Esta investigación presenta una propuesta de análisis de los factores que fueron determinantes en la competitividad en los municipios que integran la Ruta Turística Don Vasco, incluyendo el municipio de Morelia, tomando como referencia los años 2015 y 2017, para ello se realizó un conglomerado de clústeres jerárquico, para agrupar a los municipios que comparten características en común. Para efecto de este análisis se determinaron los factores que podrían incidir en la competitividad tales como: los programas de la política pública enfocados al turismo, los servicios de atracción turística, los servicios recreativos complementarios al turismo, el servicio de transporte, la capacitación turística, la infraestructura e inversión y la calidad en infraestructura. Posteriormente se determinó que los municipios que cuentan con una mayor infraestructura en estos rubros antes descritos son Morelia como líder, le sigue Uruapan, Pátzcuaro y Zamora. Mientras que los municipios que obtuvieron un menor desempeño son Ziracuaretiro y Tingambato, los cuales representan deficiencias en infraestructura en general. Con base en lo expuesto con antelación se hacen las propuestas en materia de turismo encaminadas a ¿cómo lograr una mejoría y desempeño de los municipios que presentan dicha problemática?
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2020-0661; Clústeres jerárquico; Turismo; Ruta Don Vasco; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2681